2017
DOI: 10.1097/ico.0000000000001102
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross-Linking for Keratoconus in Pediatric Patients—Long-Term Results

Abstract: CXL remains effective in stabilizing keratoconus for longer than 2 years in a majority of pediatric eyes. Flattening of Kmax was greater in moderately advanced keratoconus and central cones. Long-term follow-up beyond 4 years, however, revealed that a few eyes showed features suggestive of reversal of the effect of CXL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 21 publications
4
51
2
3
Order By: Relevance
“…We also demonstrated continuous improvement in corneal topographic values with significant flattening of both Kmax and Kmin a year following CXL procedure; however, slight steepening was noticed after two years for available patients (eight eyes). This is in accordance with the results of previous studies with a follow-up duration ranging from one to three years [16]. Improvement in keratometric values was associated with significant decrease of ABFS suggesting global corneal flattening as well.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also demonstrated continuous improvement in corneal topographic values with significant flattening of both Kmax and Kmin a year following CXL procedure; however, slight steepening was noticed after two years for available patients (eight eyes). This is in accordance with the results of previous studies with a follow-up duration ranging from one to three years [16]. Improvement in keratometric values was associated with significant decrease of ABFS suggesting global corneal flattening as well.…”
Section: Discussionsupporting
confidence: 92%
“…Although the main objective of CXL treatment is to prevent keratoconus progression, flattening of the cornea is commonly reported [7,15]. In ours, as well as in similar studies [8,16], initial steepening of both keratometric indices, Kmax and Kmin was observed during the first three months. This has been suggested to be the result of early epithelial remodeling [17].…”
Section: Discussionsupporting
confidence: 76%
“…Caporossi et al and Zotta et al [71, 72] reported stable efficacy at 3-year follow-up. More recent studies report stabilization in visual parameters at 4-year follow-up, including improvement in corrected distance vision (CDVA) in 69.1% of treated patients and a decrease in Kmax by 1.4 D ( p = 0.04) [69, 73, 74]. At 5-year follow-up, Godefrooji et al [75] showed improvement in maximum keratometry by mean of −2.06 diopters, p = 0.01.…”
Section: Results With Cross-linkingmentioning
confidence: 99%
“…[28][29][30] CXL has been proved in its effectiveness and safety in halting the progression of keratoconus and improving topographic and visual parameters in numerous prospective, published studies, including randomized controlled trials. [31][32][33][34][35][36] However, given the prolonged irradiation time of this standard CXL (SCXL) protocol, with total treatment times in excess of 1 hour, researchers have proposed accelerated CXL (ACXL) protocols, to improve convenience and comfort for patients. These ACXL protocols have the aim of decreasing UVA exposure time by increasing UVA fluency to achieve the same overall total UVA dosage.…”
mentioning
confidence: 99%